Geology and fault analysis of Lembang West Java, Indonesia - Nur Najihah Jamari (2018)
This research was done in Lembang, which located in West Java, Indonesia. Study area is located at coordinate with latitude 06°48'6.929" to 6°50'47.288" South and longitude l07°35'53.702" to l07°38'35.419 east. Geological mapping is conducted in area of 25km2 in Lembang to make a detailed observation of geology and fault analysis of the research area. Lithology, geological structure and strike and dip measurement have been measured and recorded. Raw data taken in the ﬁeld is analysed using GIS software, rose diagram software and stereonet. The study area consists of andesite that intrudes the older volcanic breccias, breccias luff, pumiceous ruff and sandy tuff. Lembang Fault is an active major fault in the study area and West Java. From the dynamic and kinematic analysis, the fault is identiﬁed as dextral- nomial oblique fault. Major extensional joint is in direction of 10°-30° and 190°- 210° and the major shear stress is from 270° to 90° of azimuth direction.